Molecular assessment among intra and inter-species of durian using PCR-RFLP of choloroplast and ribosomal DNA. - Santoso, Panca Jarot; Saleh, Ghizan (Universitas Brawijaya. Fakultas Pertanian, 2009)
A study to assess the genetic variations of durian germplasm based on Polymerase Chain Reaction - Restricted Fragment length Polymorphism (PCRRFlP) of chloroplast DNA and ribosomal DNA regions was conducted at Genetics and Plant Breeding lab., Faculty of Agriculture, UPM from November 2001 to May 2003. PCR-RFLP on the ndhC-tmV and rbcL regions, using eight restriction enzymes, was conducted to study genetic variation among 11 accessions of 10 Durio species. Based on PCR-RFLP of the ndhC-tmV region, the 11 accessions of Durio species were grouped into five distinct clusters, where the accessions generally showed high variations. Based on PCR-RFLP on the rbcL region, the accessions were grouped into three distinct clusters, and generally showed low variations. PCR-RFLP on the ndhC-tmV cpDNA and IGS-rDNA regions of durian DNA from 71 cultivated clones were found to have produced only monomorphic bands, indicating that mutation or alteration has not occurred on the pattern of their sequences. PCR-RFLP on the chloroplast DNA (rbeL and ndhC-tmV regions) can therefore, be considered as useful marker in investigations of the genetic variation of durian at inter-species level or higher taxa, other than at intra-specific level, and presumed so do the intergenic spacer of ribosomal DNA (IGS-rDNA region).